Comparative study of diradical characters and third‐order nonlinear optical properties of linear/cyclic acenes versus phenylenes. Issue 4 (16th March 2012) - Muhammad, Shabbir; Minami, Takuya; Fukui, Hitoshi; Yoneda, Kyohei; Minamide, Shu; Kishi, Ryohei; Shigeta, Yasuteru; Nakano, Masayoshi; Nakai, Hiromi; Yoshizawa, Kazunari; Ando, Koji; Nakajima, Takahito; et al.
Abstract A long‐range corrected spin‐unrestricted density functional theory (LC‐UDFT) approach has been used to investigate the diradical character (yi) and third‐order nonlinear optical properties of linear/cyclic [N]acenes and [N]phenylenes in their ground states, where N is the number of benzene rings in each linear and cyclic configuration. It has been found that linear and cyclic acenes with N = 5–10 show singlet diradical characters, while linear and cyclic phenylenes with equivalent number of benzene rings have closed‐shell configurations. The amplitudes of third‐order nonlinear optical polarizability (γzzzz) for open‐shell linear/cyclic acenes are larger especially in intermediate range of diradical character than those of closed‐shell phenylene counterparts. For example, the γzzzz values of [5]cyclic acene (y0 = y1 = 0.320) is 4.89 × 103 a.u. which is about 6 times larger than those of 0.80 × 103 a.u. for closed‐shell [5]cyclophenylene. Similarly, γzzzz value of [5]linear acene is also about 9 times larger than its closed‐shell [5]linear phenylene counterpart. Our results show interesting insights into the relationship among the architectures, diradical characters and γzzzz values of different acenes and phenylenes. © 2012 Wiley Periodicals, Inc.